2012
DOI: 10.1007/s12263-012-0319-1
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates high-glucose-induced hyperpermeability mediated by caveolae via VEGF/KDR pathway

Abstract: Endothelial hyperpermeability induced by hyperglycemia is the initial step in the development of atherosclerosis, one of the most serious cardiovascular complications in diabetes. In the present study, we investigated the effects of resveratrol (RSV), a bioactive ingredient extracted from Chinese herb rhizoma polygonum cuspidatum, on permeability in vitro and the molecular mechanisms involved. Permeability was assessed by the efflux of fluorescein isothiocyanate (FITC)-dextran permeated through the monolayer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…Our former work found Res ameliorated hyperpermeability via VEGF/KDR pathway [41]. Additionally, investigations suggest that Res was one of the earliest identified energy-restriction mimetic agents (ERMAs) via SIRT1-dependent activation of AMPK [42], [43], and SIRT1 could activate eNOS and increase NO production and thus leads to endothelium-dependent vasodilation [44].…”
Section: Discussionmentioning
confidence: 98%
“…Our former work found Res ameliorated hyperpermeability via VEGF/KDR pathway [41]. Additionally, investigations suggest that Res was one of the earliest identified energy-restriction mimetic agents (ERMAs) via SIRT1-dependent activation of AMPK [42], [43], and SIRT1 could activate eNOS and increase NO production and thus leads to endothelium-dependent vasodilation [44].…”
Section: Discussionmentioning
confidence: 98%
“…Resveratrol modulates this interaction at two different levels: downregulation of Cav‐1 expression and inhibition of Cav‐1–eNOS association. These effects of resveratrol have been observed in vivo in the rat heart and in cultured endothelial cells . The downregulation of Cav‐1 (which takes hours to days) is likely to be mediated by HO‐1, whereas the acute reduction of the Cav‐1–eNOS association (which occurs within minutes) is likely to be due to Src kinase–mediated Cav‐1 phosphorylation on Tyr14 and dependent on stimulation of estrogen receptors …”
Section: Resveratrol Improves Endothelial Functionmentioning
confidence: 92%
“…In this study, we found that after neonatal MSG treatment, PV1 protein expression showed a strong tendency to increase in all studied regions in adulthood, with a significant increase in the CMC (Figure 1c). In this regard, some studies suggest that BBB disruption is more related to an increase in the endothelial transcytosis rate, rather than the loss of tight junctions (Reeson et al, 2015; Tian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%